Inclusivity of Sexuality Education and Gender Equality from a Humanistic Philosophical Perspective: A Case Study in an Urban Primary School - Hendarwati, Endah; Ichda Wahyuni, Holy (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Sexuality education and gender equality at the primary school level still face various structural, cultural, and pedagogical challenges, particularly within the context of urban Indonesian society. This article aims to analyze the implementation of sexuality education and gender equality in primary education practice through a humanistic philosophical approach. This study employed a qualitative-philosophical method using a case study involving six teachers in primary schools in Surabaya. Data were collected through in-depth interviews and analyzed using Fairclough’s critical discourse analysis. The findings indicate that sexuality education has been present in a hidden and euphemistic form, such as girls’ counseling sessions or extracurricular activities, but has not yet been delivered explicitly, inclusively, or in a gender-equitable manner. There is evident gender role bias in teaching practices, which highlights teachers’ weak reflective awareness of equality values. The humanistic approach offers an ethical and pedagogical framework capable of reconstructing educational practices by positioning children as autonomous individuals who have the right to knowledge, protection, and respect for diversity. This article proposes the need for a transformation towards sexuality education grounded in humanistic values to foster a more empathetic, just, and contextually relevant education system.